Fiction as resistance : the post-9/11 novel as an alternative to the dominant narrative : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, Albany, New Zealand - Lee, Kathryn Mary Elizabeth (Massey University, 2012)
This thesis explores three post-9/11 novels, namely Don DeLillo's Falling Man, Mohsin Hamid's The Reluctant Fundamentalist, and Ian McEwan's Saturday, in terms of their resistance to the dominant narrative that overtook the media and political rhetoric in the days after September 11, 2001. I demonstrate how, through this resistance, the novels create spaces for the reader to re-examine and re-imagine the causes for, consequences of, and responses to 9/11. There are three aspects of this dominant narrative: America the Brave – although Americans suffered huge loss of life and significant trauma, the media and government agencies focused firmly on the heroics of the days surrounding the events rather than the more uncomfortable or tragic elements. The second aspect is one that was clearly stated by President Bush when he said “You are with us, or you are with the terrorists.” The third aspect is that of America as innocent victim and the terrorists as evil perpetrator. DeLillo's Falling Man principally disrupts the dominant narrative by reinstating Richard Drew's censored photograph, the Falling Man, thereby rectifying the undemocratic editing of what was to be included in the photographic history of 9/11. Hamid's The Reluctant Fundamentalist gives centre stage to Changez, a Pakistani male who represents those of Middle Eastern descent whose voices were elided from the dominant narrative. Ian McEwan's Saturday troubles the conceptualisation of invasion through the characters of Perowne and Baxter. Perowne represents Western privilege and Baxter, despite being English, stands for the evil outsider. This notion of invasion is troubled through questioning who is at fault for the invasion of the Perowne household by Baxter and his friends and through the invasion of Baxter when Perowne operates on him after throwing him down the stairs. By reinstating the suppressed images, giving voice to silenced sections of society and questioning of the motives and intentions of those in power, these three novels work to resist the dominant narrative's powerful hold over the general public and provide the imaginative space for new possibilities, new perspectives and critical engagement with 9/11 and the responses to it.
Keywords: Post-9/11 literature; Don DeLillo; Mohsin Hamid; Ian McEwan; Falling man (novel); The reluctant fundamentalist (novel); Saturday (novel); Dissent in literature; 9/11 in fiction; Dominant narrative